The Use of Reward and Punishment in Classroom Management in Elementary Schools - Iskandar, Sofyan; Rosmana, Primanita Sholihah; Agnia, Adela; Safitri, Rayi; Gustavisiana, Tegar Selaras (PT. Anagata Sembagi Education, 2024)
This article discusses the use of rewards and punishments in managing classrooms in elementary schools, which are common strategies for teachers to manage student behavior and create a conducive learning environment. Rewards are given as a form of appreciation for students' positive behavior, while punishment is used to reduce negative behavior. Based on literature studies, the use of rewards can increase learning motivation and strengthen positive behavior, while punishment can reduce deviant behavior and increase discipline in the classroom. However, teachers must use rewards and punishment proportionally and fairly so as not to have a negative effect on students. This article also discusses effective strategies for implementing rewards and punishment, as well as the importance of consistency in managing the classroom.